Antiviral activity of monoterpenes beta-pinene and limonene against herpes simplex virus in vitro - Astani, Akram (Iran J Microbiol, 2014)
BACKGROUND AND OBJECTIVES: Essential oils are complex mixtures containing compounds of several different functional- group classes. Depending on the structure, we can distinguish monoterpenes, phenylpropanes, and other components. Here in this study two monoterpene compounds of essential oils, i.e. β-pinene and limonene were examined for their antiviral activity against herpes simplex virus type 1 (HSV-1) in vitro. MATERIAL AND METHODS: All antiviral assays were performed using RC-37 cells. Cytotoxicity was determined in a neutral red assay, antiviral assays were performed with HSV-1 strain KOS. The mode of antiviral action was evaluated at different periods during the viral replication cycle. Acyclovir was used as positive antiviral control. RESULTS: Beta-pinenene and limonenen reduced viral infectivity by 100 %. The mode of antiviral action has been determined, only moderate antiviral effects were revealed by monoterpenes when these drugs were added to host cells prior infection or after entry of HSV into cells. However, both monoterpenes exhibited high anti-HSV-1 activity by direct interaction with free virus particles. Both tested drugs interacted with HSV-1 in a dose-dependent manner thereby inactivating viral infection. CONCLUSIONS: These results suggest that monoterpenes in essential oils exhibit antiherpetic activity in the early phase of viral multiplication and might be used as potential antiviral agents.